Using Remote Sensing Coupled with Analytic Hierarchy Process Approach for Evaluating Water Harvesting in Baglia Site - Fakher, Zahraa R.; Al-Mulla, Sahar T.; Jassem, Riaed S. (Iraqi Journal of Science, 2022)
This research involves the application of spectral indices and GIS techniques coupled with the Analytic Hierarchy Process, to assess  Baglia site, eastern Missan, as a water harvesting potential site. The AHP and pairwise comparison have been used through select four criteria including TWI, TRI, MNDWI, and NDSI, which were deemed as impact factors for this study. All these criteria have been weighted according to their significance in the water harvesting system. The findings of the AHP analysis method explained that the WH potential zones in Baglia site were divided into three zones, namely, high,  medium, and low suitability. The findings demonstrate that  Bglia site, where the highly appropriate zone is located in the deep valley area, is the ideal location for setting up water harvesting operations. The low suitability zone, in contrast, is located in a higher terrain when there is a steep slope area.